Nkanelo wa mathyelo ya mavito ya mitlawa ya vatirhi ehansi ka masipala wa Bohlabela eka xifundzankulu xa Mpumalanga, eAfrika Dzonga : maendlelo ya onomasitiki - Ndlovu, J. (My University, 2024)
Names and naming processes often portray the culture and history of a particular people. Hence, names and naming are intertwined with a given society’s practices and behavioural patterns. Embedded in such is also people’s ways of life and philosophy. In the African context, names are often laiden with meanings, most of which may not be necessarily obvious to a person who is not as well-versed in a given people’s onomastic practices and creativity. Names of Working Groups are not an exception in this regard. By Working Groups, it is meant here groups of people who work in collaboration to achieve a particular goal together. Such groups often use a particular name to identify themselves in society, and in their naming themselves, one realises that there is a meaning behind the name. Accordingly, this research study aimed at analysing Working Groups’ names in the Municipality of Bohlabela, in the Mpumalanga Province of South Africa. Qualitative in approach and underpinned by Attribution Theory, the study explored the names of Working Groups as potent tools to cause conflict among members of Working Groups, and equally as models that empahasise communal trust, discipline and support among the members of these groups.
An analysis of the names of Working Groups in Bohlabela Municipality in Mpumalanga Province, South Africa : an onomastic approach
Thesis (M. A. (African Languages)) -- University of Limpopo, 2023
Keywords: Onomastic; Name; Naming; Names, Ethnological; Onomasiology